Strategic support from business incubators: Unveiling their impact on entrepreneurial success in Malaysia’s start-ups - Mohd Noor Hidayat Jimainal; Nor Afifah Yusof; Khairiah Mazdiah Kalimin; Suddin Lada; Brahim Chekima; Rudy Ansar; Ming Fook Lim; Ramraini Ali Hassan; Faerozh Madli; Kelvin Yong (Human Resource Management Academic Research Society (HRMARS), 2024)
The objective of this study is to examine the influence of business incubators' business support and infrastructure on the success of early-stage companies in Malaysia. The performance of early-stage companies may not be adequately assessed due to certain perceived deficiencies. Consequently, there is ongoing debate regarding the extent to which the components of a business incubator effectively contribute to the success of early-stage companies. The study's respondents consist of entrepreneurs who have completed programs at business incubators in Sabah, Sarawak, Johor, Kuala Lumpur, Selangor, and Penang. The analysis will be based on 100 questionnaires and will utilize the Structural Equation Modeling (SEM) technique employing Partial Least Squares (PLS). The findings of this research may be valuable for policymakers and government authorities in establishing benchmarks and may also provide business incubators with insights into the entrepreneurs within their programs. Additionally, other researchers can utilize this study as a point of reference for future investigations in related fields of study.